Síntese de heteroestruturas TiO2/BiVO4 via "blocos de construção" para aplicação em fotocatálise heterogênea - Soares, Fernando Camargo (Universidade Federal de São Carlos, 2020)
Two environmental problems of great importance today are the release of organic contaminants in aquatic bodies and Carbon Dioxide (CO2) in the atmosphere. The first problem is associated with increased industrial and agricultural activity, which releases contaminated effluents into aquatic bodies. CO2 is one of the main responsible for the Greenhouse Effect, however, it is essential for life, participating in the photosynthesis process. Due to CO2 excess, decomposition methods or possible uses are necessary. Heterogeneous Photocatalysis (HF) using nanostructured semiconductors as heterostructures are a great option for the degradation of contaminants in aqueous media and to CO2 conversion. As an alternative to TiO2, which has high recombination rate and of being excited only with radiation from the ultraviolet region, heterostructures have the potential for application in HF processes, both for oxidative and reduction process. Based on the above, this work aimed at the synthesis of TiO2/BiVO4 heterostructures for application in HF. As a way to obtain greater control of the synthesis, these synthesized by “Building Blocks”, using the crystallized components as heterostructures precursors. It was studied the TiO2/BiVO4 system with different proportions in order to find the best Ti: Bi ratio to increase efficiency and selectivity. These heterostructures were characterized by X-Ray Diffractometry (XRD), Scanning and Transmission Electron Microscopy (SEM and MET), Fourier Transform Infrared Spectroscopy (FTIR), Diffuse Reflection Spectroscopy (DRS) and N2 adsorption at low temperatures (BET method). The photodegradation of Methylene Blue dye in water using UV radiation and photoreduction of CO2 in the gas phase using visible radiation it was applied for these materials. The results showed that heterostructures were more efficient than isolated materials, an indication of their formation. Besides, the proportion between semiconductors and treatment time has influenced the efficiency, showing that the interface formation must be dependent on kinetic parameters in the synthesis.
Synthesis of heterostructure TiO2/BiVO4 via "buiding blocks" for application in heterogeneous photocatalysis
Keywords: Fotocatálise Heterogênea.; Fotorredução de CO2.; Fotodegradação.; Heteroestruturas.; Semicondutor.; CO2 Photoreduction.; Heterogeneous Photocatalysis.; Heterostructure.; Photodegradation.; Semiconductor.; CIENCIAS EXATAS E DA TERRA